Impact of Financial Literacy on Saving Decisions: Insight from Aseman Project Operated by Barkat Foundation - VAhid Moghadam; Hadi Amiri; Sahar Baharipour; Fatemeh Bagheri; Parisa GHasemian (Journal of Asset Management and Financing)
This study investigated the impact of financial education on the saving decisions of members in the microfinance funds of Aseman Project operated by Barkat Foundation. Specifically, it examined how fund membership affects individuals' financial knowledge and attitudes and how these in turn influence the quality of their saving behaviors. The research data were collected through structured interviews and analyzed using the Partial Least Squares-Structural Equation Modeling (PLS-SEM) technique. The findings indicated that financial knowledge had a significant positive effect on saving attitudes and behaviors. Membership in the microfinance funds was found to positively influence the participants' levels of financial knowledge and attitudes, but did not have a direct significant effect on their saving behaviors. This suggested the training provided by the microfinance institution impacted knowledge and attitudes, but did not lead to visible changes in saving behaviors and, consequently, poverty alleviation. While financial literacy is typically viewed as formal training provided to individuals, this study highlighted how membership in financial support programs could also shape financial knowledge and decision-making. This often overlooked pathway deserves greater attention in financial education research and practice.Keywords: Microfinance, Financial Literacy, Saving Decision-Making, Structural Equations, Propensity Score. IntroductionOne of the key debates around poverty alleviation centers on the "poverty trap" - the idea that increasing the incomes of the poor is essential for helping them escape this cycle (Easterly, 2006). Some believe that global aid can effectively lift people out of poverty, allowing them to solve their own problems (Sachs, 2005; Banerjee & Duflo, 2011). Others argue that such aid can create a culture of dependency, actually making the poor poorer and preventing assistance from reaching the right channels (Biglaiser & McGauvran, 2022; Banerjee & Duflo, 2011).Microfinance, which aims to provide sustainable access to financial resources rather than direct spending, has not yielded significant evidence of helping the poor escape the poverty trap (Adams et al., 1984; Bateman, 2010; Morduch, 2000; Banerjee et al., 2015). This may be partly due to the poor making suboptimal financial decisions in using the received funds - a problem often attributed to their low levels of financial knowledge (Wise, 2013).The lack of financial literacy among the poor underscores the need for financial education (Kaiser et al, 2022). Improving the quality of saving decisions is also considered crucial for empowerment and self-sufficiency (Rink & Barros, 2021). In other words, financial knowledge can enable better management of limited financial resources (Atlas et al., 2019). This study tested the hypothesis that the financial education provided through Aseman project operated by the microfinance institution of Barkat Foundation had increased the financial literacy of its members. Materials & MethodsThe study sample consisted of 113 individuals aged 18 years and above selected from 4 villages (Sohrofiroozan, Tad, Ardal, and Bajgerd) that were part of Aseman Project's microfinance fund member population of 185 people. Data were collected through semi-structured interviews and observations using a questionnaire as the primary data collection tool. The questionnaire was designed based on previous financial literacy research (Hogarth & Hilgert, 2002; Lusardi & Mitchell, 2011; Mandell, 2008; OECD, 2013) and consisted of two main parts. The first part measured financial knowledge using the core OECD financial literacy questionnaire (OECD, 2013).The reliability and validity of the variables (financial knowledge, saving attitude, and saving behavior) were assessed using Cronbach's alpha, Fornell and Larcker's method, and the SmartPLS2 software. The results showed Cronbach's alpha and composite reliability values above 0.7 for all variables, thus indicating acceptable reliability.To evaluate the impact of Aseman Project, the study examined the effect of microfinance fund membership on the dependent variables of financial knowledge, saving attitude, and saving behavior. One crucial step in policy evaluation is to ensure comparability between treatment and control groups. The Propensity Score Matching (PSM) method was used to achieve this with the PS match command in Stata software applied to compare outcomes between the two groups. FindingsThe results showed that the index of saving attitude had an R-squared value of 0.95 for the dependent variable of saving behavior, indicating that the model explained a significant proportion (95%) of the variance in saving behavior. The Q-squared index, which measured the model's predictive power, had a value of 0.19 for the variable of saving attitude, suggesting moderate predictive power. For the variable of saving behavior, the Q-squared value was a strong value of 0.41.The path coefficients and significance levels revealed several key relationships: 1) Saving knowledge had a significant positive effect on saving attitude with a path coefficient of 0.53 (p<0.05). A one-standard-deviation increase in saving knowledge led to a standard deviation increase of 0.53 in saving attitude, 2) Saving knowledge also had a significant positive effect on saving behavior with a path coefficient of 0.26 (p<0.05). A one-standard-deviation increase in saving knowledge led to a standard deviation increase of 0.26 in saving behavior, and 3) Saving attitude had a significant positive effect on saving behavior with a path coefficient of 8.01 (p<0.05). A one-standard-deviation increase in saving attitude led to a standard deviation increase of 8.01 in saving behavior.The propensity score matching analysis revealed a positive and statistically significant effect of microfinance fund membership of Aseman Plan on saving knowledge. Specifically, the estimated treatment effect was 0.25, which was significant at the 5% level (t =1.96). These findings supported the first hypothesis, indicating that fund membership increased the participants' saving knowledge. Similarly, the analysis found a positive and significant treatment effect of 0.38 (t-statistic=2.26) on saving attitude at the 5% probability level. This result provided support for the second hypothesis, demonstrating that membership in Aseman microfinance funds enhanced the participants' saving attitudes. In contrast, the estimated treatment effect on saving behavior was positive (0.17) but not statistically different from zero. Consequently, the third hypothesis, which anticipated a significant effect of fund membership on saving behavior, had to be rejected based on the empirical evidence. Discussion & ConclusionThe findings indicated that membership in the microfinance funds of Aseman Plan, which represented a form of saving-related decision making, had a positive impact on both saving knowledge and saving attitude among members. This supported the first two hypotheses of the study. Specifically, the results confirmed the relationships between saving knowledge and saving attitude, as well as saving attitude and saving behavior. Membership in the microfinance funds of Aseman Plan was found to significantly improve the levels of saving attitude and saving knowledge for members compared to non-members. However, the analysis did not detect a significant effect of fund membership on actual saving behavior. This suggested that while the program had been successful in enhancing financial literacy and positive saving-related mindsets, it had not yet translated into tangible changes in saving practices and outcomes.Despite the lack of a direct impact on saving behavior, the findings indicated that Aseman Plan had ancillary benefits in terms of improving financial knowledge and attitudes among participants. This "side effect" of increased financial literacy could potentially have long-term, intergenerational impacts that went beyond the immediate poverty alleviation objectives of the microfinance program.One limitation of the study was challenges in accessing and communicating with fund officials and members to conduct interviews. Future research should explore these intergenerational effects and seek to understand how the quality and quantity of financial education provided to members can be enhanced to better translate into improved saving behaviors. The key practical implication is that policymakers and program administrators should place greater emphasis on the quality and delivery of financial literacy training within microfinance initiatives. Strengthening this educational component may be crucial for maximizing the downstream impacts on actual saving outcomes and financial well-being.